512 Terminally exhausted CD8+ T cells potentiate the tolerogenic tumor microenvironment as functional suppressors. (9th November 2020) - Vignali, Paolo; DePeaux, Kristin; Watson, McLane; Menk, Ashley; Scharping, Nicole; Delgoffe, Greg
Abstract : Background: Blockade of co-inhibitory 'checkpoint' molecules, PD-1 and CTLA-4, has induced impressive clinical responses in advanced tumors; yet only in a subset of patients. 1–3 Limited success with checkpoint blockade therapy suggests other cell extrinsic or intrinsic mechanisms may be dampening an effective immune response. Cytotoxic CD8+ T cells (CTL) encountering chronic antigen and metabolic restriction can differentiate to a terminally exhausted state (Texh), marked by hyporesponsiveness and metabolic, epigenetic, and transcriptional dysfunction. 4–8 While enrichment of this population in tumor is a negative prognostic factor, 9–10 it remains unclear whether Texh are simply non-functional or instead possess tolerogenic or suppressive properties. Transcriptional profiling of tumor-infiltrating PD-1int (progenitor exhausted) CTL versus PD-1hiTIM-3+ (terminally exhausted; Texh), reveals that exhausted cells express a pattern of genes associated with immune suppression. We hypothesize that Texh potentiate the suppressive microenvironment of solid tumor by autoregulation and inhibition of local immune responses. Methods: T cell populations were isolated from murine melanoma–B16-F10 or a lab-generated melanoma clone of the spontaneous BREF/PTEN model–by expression of inhibitory receptors and assayed in tandem in microsuppression assays. Murine melanoma clones with inhibited oxidative metabolism were generated by CRISPR-Cas9 deletion and validated for ablated mitochondrial respiration by extracellular flux analysis. Enforced expression of CD39 in effector T cells was attained by murine retroviral vector delivery. Results: When sorted directly from tumor, PD-1hiTim3+ Texh, but not progenitor exhausted PD-1int CTL, induce marked suppression of T cell effector responses, comparable to Foxp3+ Treg from the same environment. Expression of the ectonucleotidase, CD39, is uniquely expressed in Texh and increases as T cells differentiate towards exhaustion. Genetic deletion of CD39 in Texh eliminates the regulatory phenotype of tumor-infiltrating Texh and enforced CD39 expression on effector T cells can inhibit T cell receptor signaling and downstream function. CD39 expression correlates with exposure to hypoxia and Texh sorted from tumors engineered to be less hypoxic displayed a significant loss of suppressive capacity. Our data suggest that tumor hypoxia enforces Hif1a-dependent expression of CD39 which depletes extracellular ATP, contributes to generation of immunosuppressive adenosine, and has been previously associated with terminal exhaustion. 11–13 Conclusions: Our data support a model that as CTL progress to terminal exhaustion, hypoxic exposure enforces the upregulation of CD39, providing Texh a mechanism to suppress proinflammatory processes. These findings suggest Texh are not solely dysfunctional but rather are deleterious to anti-tumor immunity and may need to be drastically reprogrammed or deleted in order to alleviate immunosuppressive functions. References: Wolchok JD. et al. Overall survival with combined nivolumab and ipilimumab in advanced melanoma. N. Engl. J. Med 2017; 377, 1345–1356. Hellmann MD, et al. Nivolumab plus ipilimumab as first-line treatment for advanced non-small-cell lung cancer (CheckMate 012): results of an open-label, phase 1, multicohort study. Lancet Oncol 2017; 18, 31–41. Robert C. et al. Pembrolizumab versus ipilimumab in advanced melanoma. N. Engl. J. Med . 2015; 372, 2521–2532. Miller BC, et al. Subsets of exhausted CD8+ T cells differentially mediate tumor control and respond to checkpoint blockade. Nat. Immunol 2019;20:326–336. Im SJ, et al. Defining CD8+ T cells that provide the proliferative burst after PD-1 therapy. Nature 2016;537:417–421. Blackburn SD, Shin H, Freeman GJ & Wherry EJ. Selective expansion of a subset of exhausted CD8 T cells by alphaPD-L1 blockade. Proc. Natl. Acad. Sci 2008;105:15016–15021. Pauken KE, et al. Epigenetic stability of exhausted T cells limits durability of reinvigoration by PD-1 blockade. Science 2016;354:1160–1165. Najjar YG, et al. Tumor cell oxidative metabolism as a barrier to PD-1 blockade immunotherapy in melanoma. JCI Insight. 2019; 4. Loo K, et al. Partially exhausted tumor-infiltrating lymphocytes predict response to combination immunotherapy. JCI Insight 2017; 2. Daud AI, et al . Tumor immune profiling predicts response to anti-PD-1 therapy in human melanoma. J. Clin. Invest 2016;126:3447–3452. . Duhen T, et al . Co-expression of CD39 and CD103 identifies tumor-reactive CD8 T cells in human solid tumors. Nat. Commun 2018;9:2724. Canale FP, et al . CD39 Expression defines cell exhaustion in tumor-infiltrating CD8+ T Cells. Cancer Res 2018;78:115–128. Gupta PK, et al . CD39 expression identifies terminally exhausted CD8+ T cells. PLoS Pathog 2015;11, e1005177.